Effect of supplementing feed grade L-methionine in plant sourced diet on the performance of broiler chicken (Bangladesh Journal of Livestock Research, 2021)
The study was conducted to investigate the productivity and profitability of broiler on L-methionine supplemented diet. A total of 160 day-old broiler chicks (Cobb 500) was randomly distributed to four dietary supplements, D0 (Control), D1 (0.30 % L-Met), D2 (0.35 % L- Met) and D3 (0.40 % L- Met). Each treatment was replicated five times with 8 birds per cage. The chicks were reared in the battery cages while they were fed with broiler starter diet (crumble) until Day14 of age. The birds with fed with L-Met supplemented diets starting from Day15 until Day35 of age All the diets were iso-caloric and iso-nitrogenous.. Results revealed that the L-Met supplementations were in favor of higher live weight (LW) and better (p0.05) difference was observed in the relative weights of visceral organs (small intestine, proventriculus, gizzard, liver and heart) except for the spleen. Relatively increased (p